Professionalization of action sports: field- and organizational-level professionalization of new Olympic sports - Choi, K. H.; Byun, J. (Sport in Society: Cultures, Commerce, Media, Politics, 2024)
The inclusion of action sports in the Olympic Games and gaining popularity may necessitate a professionalization of the associated sports organizations to effectively tackle the challenges and meet the expectations of various stakeholders. This study explores the professionalization of action sports newly included in the Olympics by focusing on skateboarding and surfing in South Korea. Data for this study included semi-structured interviews with key individuals (n = 17) and archival materials. The findings indicate that Olympic inclusion triggered the sports` professionalization at the field- and organizational-levels. There were changes in the institutional environment for the sports at the field-level, and the sports` central organizations underwent structural and procedural changes. This research provides implications to action sports organizations and stakeholders, especially those in countries where action sports are less popular, who wish to leverage the Olympic inclusion of their sports as an opportunity to establish a more professionalized system for sports.